(untitled) (International Journal of Management Trends: Key Concepts and Research, 2024)
This paper explores the relationship between sustainable human resource management (HRM) practices and job performance within the United Arab Emirates (UAE) healthcare industry. Drawing from the literature on sustainable HRM practices, the study examines the impact of sustainable selection processes, employee empowerment, and training on job performance. The findings reveal significant positive correlations between sustainable selection processes, employee empowerment, and train-ing with job performance. Structured interviews, internal promotion policies, and regular training opportunities were identified as key factors contributing to enhanced job performance. The study underscores the importance of sustainable HRM practices in fostering a motivated, capable, and high-performing workforce. Practical implications for organizations include developing transparent recruitment practices, providing opportunities for career progression, and fostering a culture of continuous learning and development. Future research should explore additional dimensions of sustainable HRM practices and investigate the impact of cultural factors on employee perceptions of HRM practices. Overall, this study highlights the critical role of sustaina-ble HRM practices in enhancing organizational performance and contributing to long-term success and sustainability.